Implicações do uso do solo nas propriedades físicohídricas e mecânicas de um argissolo vermelhoamarelo e de um gleissolo háplico - Mentges, Marcelo Ivan (2010)
The Central Depression is an area with sedimentary rocks, presenting a large variety of soils. In highlands Alfisols are found, whereas in lowlands Planosols and Endoaqualf. The morphological, physical and chemical characteristics define the ability of the use and management of theses soils. In the Alfisols, grain production in no-till system is a very common practice. The Endoaqualfs, because of its hydromorphic characteristics, are used for rice cultivation. In general, the agricultural use changes the soil properties. With the intention to analyze the effect of agricultural use on soil properties two studies were performed: (1) Physico-hydraulic and mechanical behavior of an Endoaqualf under different uses; (2) Soil physico-hydraulic and mechanical properties and chisel energy demand in a compacted Alfisol. Both soils are located in the experimental area of de Soil Department of the UFSM. The objective of the first study was to identify the influence of the soil use with irrigated rice in the physico-hydraulic and mechanical properties when compared to the soil maintained without agricultural use. In the second study, were evaluated the effect of soil compaction on its physicohydraulic and mechanical properties and on chisel energy demand, and to quantify the behavior of these properties below the chisel working depth. For both studies, the particle size, bulk density, porosity and soil compressibility were determined. In the first study the water retention curve was also determined. In the second study the soil resistance to mechanical penetration, the hydraulic conductivity, the area and mobilized volume and the efforts required by the chisel were also determined. The agricultural use affected the physical quality of the Endoaqualf, increasing the bulk density and reducing the macroporosity values, without cause, however, larger changes in total porosity and microporosity when compared with the treatments maintained without agricultural use. The compression index was significantly influenced by the soil bulk density, initial degree of saturation, silt content, silt + clay content and total organic carbon content, while the preconsolidation stress was not significantly affected by the soil properties evaluated. The soil use with irrigated rice did not alter the preconsolidation stress and the compression index when compared the condition of absence of agricultural use. In the second study, compaction increased both soil the bulk density and resistance to mechanical penetration, reducing the total porosity and the macroporosity, without causing significant effects in microporosity. The traffic of the 10 Mg loader reduced the susceptibility to compaction and increased the load bearing capacity to a depth of 0.20 m. The compaction increased the chisel energy demand in 21,64%, increasing the mean value of traction effort from 5,33 kN to 6,35 kN. Soil chiseling did not increase soil compaction below the chisel working depth in the Alfisol. The use of soil, generally, change the physico-hydraulic and mechanical properties, and these changes are dependent on the soil properties, mainly, how much and under what conditions the soil is used and managed.